Metabolit Sekunder Ekstrak Etanol Daun Sukun (Artocarpus altilis (Parkinson) Fosberg) dan Potensinya Sebagai Obat - Junius Gian Ginting (Journal of Natural Sciences, 2022)
Breadfruit plants have been used as traditional medicine. Parts of medicinal plants are latex, roots, bark and leaves which are used to treat fractures, sprains, diarrhea, abdominal pain, dysentery, infectious diseases, headaches, hypertension, diabetes, asthma, hepatitis, and inflammation. This study aims to determine secondary metabolites and characterization of breadfruit leaves. The research method was carried out experimentally with extraction by maceration method, and phytochemical screening on simplicia and extracts for identification of secondary metabolites. The secondary metabolites of simplicia and extracts showed the presence of flavonoid compounds, saponins and tannins. Characterization showed the presence of water content of 7.32%, water soluble extract and ethanol content of 12.29% and 8.60%, total ash content and insoluble in acid were 8.50% and 2.34%, respectively. The conclusion of the study is that the secondary metabolites of breadfruit leaves have the potential as medicinal ingredients and the simplicia characterization has met the simplicia standard.